The Influence of Interpersonal Communication on Employee Performance at the Office of the South Sulawesi Provincial Driving Teacher Center - Sri Wahyuni Syam; Muh Nasrullah; Isgunandar Isgunandar (ASHA Publishing, 2024)
The purpose of this study is to determine the influence of interpersonal communication on employee performance in the office of the South Sulawesi Provincial Driving Teacher Center. Employee performance is an important thing that can affect how much an organization's goals are achieved. Efforts to improve performance and overcome employee performance problems, of course, must be considered is the quality of good human resources so that they will be able to work optimally. Communication is an important element in improving employee performance, one of which is interpersonal communication. Interpersonal communication is the basis of effective communication for the success of an institution or organization. This study is descriptive research with quantitative techniques aimed at determining the influence of interpersonal communication on employee performance. To achieve the objectives of this research, data collection techniques are used through questionnaires and documentation. The population in this study is 89 employees with a sample of 73 employees. The data that has been obtained from the results of this study was processed using descriptive and inferential statistical analysis to determine the influence of interpersonal communication on employee performance at the South Sulawesi Provincial Teacher Driving Center office. The results of the study show that the indicators used in each variable can be concluded that interpersonal communication is in the good category and in the employee performance variable is in the good category. Based on the results of the product moment correlation test, the relationship between variables is moderate. Based on the results of a simple linear regression analysis, it was concluded that there was a positive and significant influence between interpersonal communication on employee performance at the South Sulawesi Provincial Driving Teacher Center office